CITRA DAN KEPRIBADIAN MANUSIA DALAM PERSPEKTIF PSIKOLOGI BARAT DAN PSIKOLOGI ISLAM - Meta Malihatul Maslahat (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2020)
This research aims to examine the image and personality of humans in the perspective of Western psychology and Islamic psychology. The writing method used is the qualitative method (qualitative research). As for the process of analyzing data, the authors use descriptive-analytic analysis methods. This research proves that the study of human images in Western psychology and Islamic psychology perspective have similarity. The similarity in the school of humanistic psychology, human images are seen as good beings and have unlimited potential (homo ludens). This view is compatible with the teachings of Islam and the views of Eastern people about humans. But in understanding personality, Western psychology and Islamic psychology have differences. First, in the perspective of Western psychology the study of personality is ethically neutral, that is, it only displays the personality that appears as it is. In the perspective of Islamic psychology, the study of personality is ethically laden, which is to show what personality should be. Second, in the perspective of Western psychology the study of personality only looks at the empirical aspects (environment), without looking at the inner aspects (spiritual) that underlie human personality. In the perspective of Islamic psychology, the study of personality not only looks at the empirical aspects (environment), but also looks at the inner aspects (spiritual) that underlie human personality. Third, in the perspective of Western psychology the study of anthropocentric-oriented personality, which means that the human personality is influenced by human power alone, and negate the interference or will of God Almighty. Meanwhile, the study of human personality in the perspective of Islamic psychology is anthropo-religious-centric oriented, which means that human personality is not only influenced by human power, but also there is interference or will from God Almighty.This research aims to examine the image and personality of humans in the perspective of Western psychology and Islamic psychology. The writing method used is the qualitative method (qualitative research). As for the process of analyzing data, the authors use descriptive-analytic analysis methods. This research proves that the study of human images in Western psychology and Islamic psychology perspective have similarity. The similarity in the school of humanistic psychology, human images are seen as good beings and have unlimited potential (homo ludens). This view is compatible with the teachings of Islam and the views of Eastern people about humans. But in understanding personality, Western psychology and Islamic psychology have differences. First, in the perspective of Western psychology the study of personality is ethically neutral, that is, it only displays the personality that appears as it is. In the perspective of Islamic psychology, the study of personality is ethically laden, which is to show what personality should be. Second, in the perspective of Western psychology the study of personality only looks at the empirical aspects (environment), without looking at the inner aspects (spiritual) that underlie human personality. In the perspective of Islamic psychology, the study of personality not only looks at the empirical aspects (environment), but also looks at the inner aspects (spiritual) that underlie human personality. Third, in the perspective of Western psychology the study of anthropocentric-oriented personality, which means that the human personality is influenced by human power alone, and negate the interference or will of God Almighty. Meanwhile, the study of human personality in the perspective of Islamic psychology is anthropo-religious-centric oriented, which means that human personality is not only influenced by human power, but also there is interference or will from God Almighty.